Development of Educational Game-Based Learning Media for Android Using Wordwall in Chemistry Learning Acid Base Material in Class XI of SMA N 2 Muaro Jambi - Laila Hafni Aulia Siregar; Fatria Dewi; Febbry Romundza (Mathematics Education Study Program, 2025)
The focus of this study is to create educational media through Android games centered on acidbase concepts, utilizing Wordwall. Additionally, the research seeks to assess the validity, practicality, and effectiveness of this educational media, as evaluated by content and media specialists, teacher feedback, student reactions, and examinations of the students' learning results related to the games created. The development framework employed follows the model proposed by Lee & Owens (2004), which consists of five phases: analysis, design, development, implementation, and evaluation. The study was carried out with a pilot group of 10 students from SMAN 2 Muaro Jambi. To analyze the data, both qualitative and quantitative approaches were used. The findings revealed that the educational game created was deemed valid and appropriate, achieving average validation scores of 4. 14 for material and 4 for media. The average evaluation score from practitioners was 4. 66. Results from the individual trials showed a success rate of 91. 11%, while the small group trial results achieved a percentage of 89. 86%. Furthermore, the effectiveness test of the product produced an Ngain of 0. 52, indicating a medium rating. From these outcomes, the Android game created with Wordwall was confirmed to be valid, practical, and effective, receiving favorable feedback from students during the learning process.